Riluzole Serum Concentration in Pediatric Patients Treated for Obsessive-Compulsive Disorder. Issue 6 (December 2017) - Grant, Paul; Farmer, Cristan; Song, Jane; Kish, Timothy; Swedo, Susan
Abstract: Purpose/Background: The goals of this study were to determine whether pediatric serum concentration of riluzole is similar to that observed in adults and to determine whether riluzole serum concentration is associated with adverse effects or efficacy in children and adolescents with treatment-refractory obsessive-compulsive disorder. Methods/Procedures: Data were drawn from previously published studies: 1 open-label trial and 1 randomized controlled trial with an open-label extension phase. Serum was drawn at 24, 36, and 52 weeks in 37 patients who were taking approximately 100 mg riluzole daily (mean dose at 24 weeks, 99 ± 28 mg). Findings/Results: Across all samples, serum riluzole concentration ranged from 7 to 963 ng/mL. At week 24 (n = 37), the median concentration was 76 ng/mL (interquartile range, 53–172 ng/mL). Within-patient concentration was relatively stable. One subject who had the highest serum concentration levels during the study developed pancreatitis after exiting the study. The patient had recently added fluvoxamine to the riluzole regimen. Controlling for concomitant fluvoxamine (in 6 participants) and time of draw, serum riluzole concentration was not associated with obsessive-compulsive disorder symptom severity, nor was it associated with adverse effect profile. Implications/Conclusions: The dose of riluzole used in these pediatric subjects seems to have achieved serum concentration levels similar to those observed in adults. However, as previously reported in adults, the serum concentration had no discernable relationship to efficacy or adverse effects. Abstract : Supplemental digital content is available in the text.